The role of AGG interruptions in the FMR1 gene stability: A survey in ethnic groups with low and high rate of consanguinity. Issue 10 (27th August 2019) - Manor, Esther; Gonen, Raphael; Sarussi, Benjamin; Keidar‐Friedman, Danielle; Kumar, Jay; Tang, Hiu‐Tung; Tassone, Flora
Abstract: Background: The prevalence and the role of AGG interruptions within the FMR1 gene in the normal population is unknown. In this study, we investigated the frequent of AGG loss, in one or two alleles within the normal population. The role of AGG in the FMR1 stability has been assessed by correlating AGG loss to the prevalence of premutation/full mutation in two ethnic groups differing in their consanguinity rate: high versus low consanguinity rate (HCR vs. LCR). Methods: The CGG repeat allele size and AGG presence were measured in 6, 865 and 6, 204 females belonging to the LCR (5%) and HCR (>45%) groups, respectively, by Tripled‐Primed‐PCR technique. Results: A lower prevalence of the premutation was observed in the HCR (1:158) as compared to the LCR group (1:128). No full mutation was found in the HCR females while in the LCR group the prevalence found was 1:1, 149. Homozygosity rate was higher in the HCR population compared to the LCR group.The overall AGG loss was higher in the HCR population than in the LCR and increased with increased CGG repeat number in both ethnic groups. Conclusions: Although we observed a significantly higher rate of homozygosity and AGG loss in the HCR group, this did not affect the prevalence of the premutation and full mutation in this population. Their prevalence was significantly lower than in the LCR population. Finally, we discuss whether the loss of AGG could be also a polymorphic event but not only a stabilizing factor. Abstract : A significantly higher rate of homozygosity and AGG loss has been observed in the high consanguinity rate ethnic group. However, it did not affect the prevalence of the premutation and full mutation in this population. Their prevalence was significantly lower than in the low consanguinity rate population. This points to that AGG interruption loss is also a polymorphic event mainly in the normal population.